1999
DOI: 10.1053/ejvs.1999.0870
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pregnancy on the Lower-limb Venous System of Women with Varicose Veins

Abstract: maximum changes were seen in the superficial venous system in the thigh. The effect was more pronounced on the left and the changes in reflux returned to pre-pregnancy levels in the puerperium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 22 publications
2
22
0
5
Order By: Relevance
“…17 Also, Sparey et al found that normal veins, in spite of changes in venous diameter during pregnancy comparable with that seen in those with pre-existing venous disease, return to normal after delivery, but some VVs deteriorate during pregnancy, and this may be progressive with successive pregnancies. 18 Previously, Cornu-Thenard et al had already observed a correlation between the total number of pregnancies and the size of VVs. 19 In our study, 60% of women had a history of pregnancy; however, their presence was associated with mild to moderate CVI (C 1 -C 3 ).…”
Section: Risk Factors and Concurrent Diseasesmentioning
confidence: 96%
“…17 Also, Sparey et al found that normal veins, in spite of changes in venous diameter during pregnancy comparable with that seen in those with pre-existing venous disease, return to normal after delivery, but some VVs deteriorate during pregnancy, and this may be progressive with successive pregnancies. 18 Previously, Cornu-Thenard et al had already observed a correlation between the total number of pregnancies and the size of VVs. 19 In our study, 60% of women had a history of pregnancy; however, their presence was associated with mild to moderate CVI (C 1 -C 3 ).…”
Section: Risk Factors and Concurrent Diseasesmentioning
confidence: 96%
“…19 However, this is considered unlikely owing to varices often appearing during early pregnancy when the uterus is small. 20 Another theory is that an increase in circulating hormones affects venous dilation and causes valve failure. 21 Smoking was also not a significant risk factor, which is in keeping with the lack of association found in most cross-sectional studies of varicose veins.…”
Section: Risk Factorsmentioning
confidence: 99%
“…This may be attributed to hormonal variation from the onset of menses until menopause and during pregnancy. [15][16][17][18][19][20] The prevalence of reflux in SN and TN among all the limbs studied was 1% (9/835) and of the limbs with nonsaphenous vein reflux 10.7% (9/84).…”
Section: Discussionmentioning
confidence: 91%